Intranets in French firms: evolutions and revolutions - Emmanuelle Vaast (Information Research: An International Electronic Journal)
(Progressive) evolutions and (radical) revolutions characterise the temporal paths of intranets in French firms. Based on the results of 12 case studies, this research has adopted a dynamic perspective. It has focused on the implementation and subsequent evolution of intranets, the ways they are shaped by and impact diverse aspects of organisational life, including strategic management and daily tasks. It shows that gradual and radical changes are not mutually exclusive but complementary. On the one hand, intranets evolve incrementally, by co-construction of their technical and organisational dimensions. On the other hand, they experience substantial changes aimed at interpreting them in new ways. This dual pace is noticeable in the changes intranets provide on critical organisational dimensions, such as information management and human resources policies. Finally, this dynamic perspective underscores how new balances in traditional managerial tensions may be reached as a result of these radical and progressive co-evolutions between intranets and organisations.